A Study on the Separation Length of Shock Wave/Turbulent Boundary Layer Interaction. (20th October 2019) - Zhou, Yong-yi; Zhao, Yi-long; Zhao, Yu-xin
Abstract : The separation length of shock wave/boundary layer interaction (SWBLI) was studied by a numerical method, which was validated by experimental results. The computational domain was two-dimensional (2-D). The flow field was an incident oblique shock interacting with a turbulent boundary layer on a flat adiabatic plate. According to the simulation data, the dependency of the separation length on the relevant flow parameters, such as the incident shock strength, Reynolds number, and Mach number, was analyzed in the range of 2 ≤ M ≤ 7 . Based on the relations with the flow parameters, two models of the separation length at low and high Mach numbers were proposed, respectively, which can be used to predict the extent of the separation in the SWBLI.